CRYSTAL STRUCTURE OF (Cy2NH2)2MoO4.2H2O - Serigne Fallou Pouye; Ibrahima Cissé; Libasse Diop; Kieran Christopher Molloy; Gabriele Kociok-Kohn (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2014)
The structure of this salt consists of a 3D structure. The anion interacts with NH2 group of the cation and H2O molecules respectively through N-H---O and O-H---O hydrogen bonds. The anion MoO42- is almost perfectly tetrahedral. The four values of the lengths of Mo- O bonds are all equal to 1.7613 Å (12).